Fermionic equations of motion in strongly-correlated media: applications to the nuclear many-body problem - Litvinova, Elena (2024)
These notes summarise the lectures given at the International School of Physics "Enrico Fermi" in Summer 2024 in Varenna (Italy) about the strongly coupled quantum many-body theory and its applications to nuclear structure. The lectures present a rather short overview of the subject with an emphasis on the analytical aspects of the nuclear many-body problem, aiming at a deep understanding of the complexity of strongly coupled nucleonic states and emergent collective phenomena. The major pedagogical focus is recognizing how all the models describing nuclear dynamics follow from a unified model-independent framework formulated in the universal language of quantum field theory. In particular, connections between the classes of ab initio, density functional theory, and beyond mean-field approaches are made accessible. Approximations of varying complexity are discussed in applications to excited states of medium-heavy nuclei.